A disposable molecularly imprinted electrochemical sensor for the ultra-trace detection of the organophosphorus insecticide phosalone employing monodisperse Pt-doped UiO-66 for signal amplification. Issue 9 (25th March 2020) - Xu, Liping; Li, Jiebin; Zhang, Jiajia; Sun, Junyong; Gan, Tian; Liu, Yanming
Abstract : A disposable electrochemical sensor was fabricated based on monodisperse Pt-doped UiO-66 and a mesoporous molecularly imprinted polymer to specifically detect phosalone. Abstract : In this work, a disposable molecularly imprinted electrochemical sensor was developed towards the highly sensitive and selective detection of the organophosphorus insecticide phosalone (PAS), employing a home-made carbon paste microelectrode (CPME) modified with a Zr-based metal–organic framework catalyst (Pt-UiO-66) and a mesoporous structured conductive molecularly imprinted polymer (MIP). Pt-UiO-66 octahedra with isolated dispersed Pt nanoparticle active sites were firstly incorporated into the CPME to provide a remarkably amplified signal for voltammetric determination. The mesoporous MIP was then synthesized onto the Pt-UiO-66/CPME via electropolymerization and a subsequent sol–gel process, which could bind the PAS template molecules through hydrogen bond, coordinate bonding, hydrophobic interaction, and π–π stacking interaction. Morphological, structural, and electrochemical characterization studies revealed that this nano-sized MIP provided excellent features for PAS detection, including high porosity, large surface area, enhanced electron-transport ability, greatly improved diffusion capacity, and strong recognition specificity. Therefore, the resulting sensor exhibited an outstanding linearly proportional concentration domain of 0.50 nM–20 μM, low detection limit of 0.078 nM, marked selectivity over certain interferences with similar configurations, considerable repeatability, reproducibility, and stability for the analysis of PAS. Moreover, the sensor was successfully applied for the determination of PAS in agricultural products and environmental samples with results in good compatibility with a chromatographic method, indicative of the high reliability and practicability. Such an electrochemical sensor might open a novel window for the investigation of selective sensing of small organic species from their analogues coupled with the molecular imprinting technique.